Right Ventricular Outflow Tract Electroanatomical Abnormalities Predict Ventricular Fibrillation Inducibility in Brugada Syndrome. (February 2018) - Letsas, Konstantinos P.; Efremidis, Michael; Asvestas, Dimitrios; Vlachos, Konstantinos; Georgopoulos, Stamatis; Tse, Gary; Liu, Tong; Bazoukis, George; Sideris, Antonios; Baranchuk, Adrian; Ehrlich, Joachim R.; Brugada, Pedro
Abstract : Supplemental Digital Content is available in the text.